2005
DOI: 10.1108/01437720510597667
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between organizational culture and withdrawal intentions and behavior

Abstract: Purpose -The goal of the present study is to examine the influence of five dimensions of organizational culture (i.e. job challenge, communication, trust, innovation and social cohesiveness) on employees' withdrawal intentions and behavior. Specifically, three forms of employees' withdrawal intentions (i.e. from the occupation, job, and organization), and one form of employees' withdrawal behavior (i.e. self-reported absenteeism) are examined. Design/methodology/approach -The paper investigates these relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 51 publications
3
78
0
11
Order By: Relevance
“…Therefore, an employee with a high intention to leave the organization can stop his/her occupation (Bigliardi, Petroni & Dormio, 2005). Carmeli (2005) says that previous researchers also acknowledged that the intention of withdrawal has been identified as a strong predictor of actual turnover of staff (Mobley, 1998). Decision to withdraw can also result in the actual rotation set according Mobley et al 1998;.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Therefore, an employee with a high intention to leave the organization can stop his/her occupation (Bigliardi, Petroni & Dormio, 2005). Carmeli (2005) says that previous researchers also acknowledged that the intention of withdrawal has been identified as a strong predictor of actual turnover of staff (Mobley, 1998). Decision to withdraw can also result in the actual rotation set according Mobley et al 1998;.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…Moreover, it is found that organizational culture significantly affects the innovation. This has been agreed by Carmeli (2005) that the organizational culture is one of the variables which are considered to have an important impact on innovation. Consequently, all the members in the organization must accept an innovation as a basic value, which will be shared and implemented by them (Hartman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This paper is aimed to focus on the role of organizational culture and communication element in maintaining employees' loyally in CP. As stated, both (Carmeli 2005). Ruppel and Harrington (2000) Relationship between employees' loyalty and organizational culture is described by Eskildsen and Nussler (2000) in Figure 1 below.…”
Section: Charoen Pokphand and Competitor's Offer Issuementioning
confidence: 99%